Conservation of the historical render in the Church of Nossa Senhora da Assunção in Elvas - Salema, Sofia (2012)
In this paper we present a practical case of conservation of the historical renders in the pyramidal tower of the Church of Nossa Senhora da Assunção in Elvas (Portugal), carried out by the former IPPAR (Portuguese Institute of Architectonic Heritage), now Regional Direction of Culture of Alentejo. Awareness of the value and of the risks facing these renders points towards the necessity to safeguard their material authenticity. During the works of conservation of the main façade, under the layers of non decorated recovering render, a previous decorated render, simulating stone masonry, with raised joints reproducing stone divisions and the internal structure in solid brick, was discovered. After material and historical analysis we came to the conclusion that it was highly probable that this render was contemporary to the construction of the Church and, as such, it seemed essential to conserve and restore this covering as historical evidence and cultural heritage. Treatment of the pyramidal tower render included removal of the non original recover mortars, survey of ancient materials, execution of technical and decorative scheme, surfaces’ cleaning and consolidation of the weaker original old mortars. In order to fill the gaps in the original surface, specific lime mortars, prepared with washed sand and standard grain size, were used. Restoration techniques were used to reconstitute and integrate the lacunas. These actions not only conserved the workmanship, but also reconstructed the decorative structure and a reading clarity, allowing the identification of restoration without the connotation of a mimetic integration. This joint action, only possible with the help of the conservation and restoration team, puts into evidence the possibility of continuous evaluation and learning. It is clear that, in cases where there are unknown, unpredictable factors, due to the specific work and value of the materials, it is possible to change the course of action and introduce new and improved measures to take into consideration new facts and new opportunities of preserving the cultural value of historical renders.